Surgical modalities in the treatment of vitiligo - R. Vignesh Narayan; Vishal Thakur (Pigment International)
Vitiligo presents a challenge not only in its medical management but also in its impact on patients’ psychosocial well-being. While medical therapies can halt disease progression, achieving repigmentation, especially in challenging areas, remains a hurdle. Surgical interventions, including therapeutic wounding, camouflage techniques, excision, and grafting methods, offer viable solutions. However, success hinges on assessing disease stability, with various clinical, dermoscopic, and cellular indicators employed for evaluation. Pre-procedure counselling is crucial to manage patient expectations and inform them about potential outcomes and risks. Surgical techniques range from simple excision to complex cellular grafting methods, each tailored to the individual patient’s needs and disease characteristics. Postoperative care, including appropriate dressing and follow-up, plays a significant role in ensuring successful outcomes. Newer techniques, such as automated blister epidermal micrografting and Meek micrografting, show promise in improving efficiency and outcomes. Combining traditional methods with innovations such as transverse needling and micro skin grafting enhances the repertoire of surgical options available. Overall, surgical approaches offer effective means to achieve repigmentation and alleviate the psychosocial burden of vitiligo, highlighting the importance of a multidisciplinary approach in its management.